International selection and competition in youth sport: pin the tail on the donkey or targeted intervention? - Sweeney, Liam; MacNamara, Áine; Taylor, Jamie (Frontiers in Sports and Active Living, 2023)
Across sporting contexts, there is growing debate surrounding the utility of junior international age group selection in sport. In this regard, there has been considerable focus on the age of selection, with the low conversion of athletes from junior to senior international level often used to critique the efficiency of such programmes. In this perspective article, we argue that there is a need for a more nuanced consideration of the effectiveness of international age groups in talent systems. We begin this perspective article with a synthesis of the literature pertaining to junior to senior transitions in sport, followed by the implications and opportunity cost presented by international age groups. We argue for a more contextual evaluation of international age groups relative to the performance aims of a talent system, the need for manipulation of challenge dynamics, and the resource costs of doing so (e.g., providing developmental challenges for those who have early advantage, or spreading resource amongst greater numbers for broader impact). We suggest that talent systems evaluate the opportunity cost presented by international age groups, with decisions based upon individual strategic context.